Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the expression for [tex]\( f(x) \cdot g(x) \)[/tex], we begin by analyzing the given functions:
1. [tex]\( f(x) = \sqrt{x^2 + 12x + 36} \)[/tex]
2. [tex]\( g(x) = x^3 - 12 \)[/tex]
First, simplify [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = \sqrt{x^2 + 12x + 36} \][/tex]
Notice that [tex]\( x^2 + 12x + 36 \)[/tex] is a perfect square trinomial:
[tex]\[ x^2 + 12x + 36 = (x + 6)^2 \][/tex]
Therefore,
[tex]\[ f(x) = \sqrt{(x + 6)^2} \][/tex]
Since [tex]\( \sqrt{(x + 6)^2} = |x + 6| \)[/tex], and assuming for the domain of [tex]\( x \geq -6 \)[/tex], [tex]\( |x + 6| = x + 6 \)[/tex]. Thus,
[tex]\[ f(x) = x + 6 \][/tex]
Next, calculate the product [tex]\( f(x) \cdot g(x) \)[/tex]:
[tex]\[ f(x) \cdot g(x) = (x + 6) \cdot (x^3 - 12) \][/tex]
Now, distribute [tex]\( x + 6 \)[/tex] across [tex]\( x^3 - 12 \)[/tex]:
[tex]\[ (x + 6)(x^3 - 12) = x \cdot x^3 + x \cdot (-12) + 6 \cdot x^3 + 6 \cdot (-12) \][/tex]
[tex]\[ = x^4 - 12x + 6x^3 - 72 \][/tex]
Therefore, the expression for [tex]\( f(x) \cdot g(x) \)[/tex] is:
[tex]\[ f(x) \cdot g(x) = x^4 + 6x^3 - 12x - 72 \][/tex]
Thus, the correct answer is:
C. [tex]\( x^4 + 6x^3 - 12x - 72 \)[/tex]
1. [tex]\( f(x) = \sqrt{x^2 + 12x + 36} \)[/tex]
2. [tex]\( g(x) = x^3 - 12 \)[/tex]
First, simplify [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = \sqrt{x^2 + 12x + 36} \][/tex]
Notice that [tex]\( x^2 + 12x + 36 \)[/tex] is a perfect square trinomial:
[tex]\[ x^2 + 12x + 36 = (x + 6)^2 \][/tex]
Therefore,
[tex]\[ f(x) = \sqrt{(x + 6)^2} \][/tex]
Since [tex]\( \sqrt{(x + 6)^2} = |x + 6| \)[/tex], and assuming for the domain of [tex]\( x \geq -6 \)[/tex], [tex]\( |x + 6| = x + 6 \)[/tex]. Thus,
[tex]\[ f(x) = x + 6 \][/tex]
Next, calculate the product [tex]\( f(x) \cdot g(x) \)[/tex]:
[tex]\[ f(x) \cdot g(x) = (x + 6) \cdot (x^3 - 12) \][/tex]
Now, distribute [tex]\( x + 6 \)[/tex] across [tex]\( x^3 - 12 \)[/tex]:
[tex]\[ (x + 6)(x^3 - 12) = x \cdot x^3 + x \cdot (-12) + 6 \cdot x^3 + 6 \cdot (-12) \][/tex]
[tex]\[ = x^4 - 12x + 6x^3 - 72 \][/tex]
Therefore, the expression for [tex]\( f(x) \cdot g(x) \)[/tex] is:
[tex]\[ f(x) \cdot g(x) = x^4 + 6x^3 - 12x - 72 \][/tex]
Thus, the correct answer is:
C. [tex]\( x^4 + 6x^3 - 12x - 72 \)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.